A practitioner's guide to digital platform business - Chiyachantana, Chiraphol N.; Ding, David K., 1959-; Hong, Jack J. (New Jersey : World Scientific, 2022)
'Offers new business strategies for the digital age. Compiles real-life case studies from innovative digital start-ups. Covers a wide spectrum of industries, from social enterprises to legal services, healthcare, hospitality, transport, etc. Discusses the impact of the COVID-19 pandemic on startups'--
Platform Business Model Canvas -- Lexagle (Soaring Above) -- RushOwl (A Route for Everyone) -- Trabble (Changing the Way We Travel) -- Savour! (Savouring with Savour!) -- ThriftCity (A Smarter Way to Shop) -- Friday.AI (Advancing One Friday at a Time) -- Kura Kura (The Lovable Kura) -- Drive Ride Buddy (A Digital Journey).
Includes index.
Keywords: Electronic commerce -- Singapore -- Case studies; New business enterprises -- Computer networks -- Singapore -- Case studies; New business enterprises -- Singapore -- Management -- Case studies; Business enterprises -- Technological innovations -- Singapore -- Case studies